Техніко-економічна ефективність використання на теплоелектроцентралях асинхронного режиму АСТГ - Сегеда, М. С.; Міняйло, О. С.; Покровський, К. Б.; Олійник, В. П. (Видавництво Національного університету «Львівська політехніка», 2007)
Proceeding from a modern condition of levels of a voltage in a power system it is offered among the basic actions of maintenance of a voltage in allowable limits to use on power stations asynchronous generators, economic efficiency of use asynchronous generators on thermal power station is investigated. Use asynchronous generators on thermal power station is shown, that, except for reduction of expenses by a reserve in a power system restriction on the combined generating of thermal and electric energy is removed.